Defoliation and Pre-Harvest Drop of Camu-Camu Fruits in Floodable Area - Panduro, Mario Pinedo; Lopez, Carlos Zumba; Davila, Elvis Paredes; Chung, Jose Ramirez; Rodriguez, Carlos Abanto; Valencia, Jaime Durand; Chagas, Edvan Alves; Torres, Dennis Del Castillo (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
The effect of defoliation and gibberellic acid (GA3) on the fall of the fruit in the induced period of harvest of Myrciaria dubia (camu-camu), in a flooded area on the banks of the Amazon River, Iquitos-Peru, was evaluated. The soil is clayey-silty with 2.15% organic matter, pH 6.29, 0.10% Nitrogen, 40.76 ppm Phosphorus and 228 ppm potassium. The average temperature is 27.45 ° C, relative humidity of 86% and 3111.4 mm of rain. The defoliation was carried out with NaCl solution in water (50 g.L-1). GA3, was applied every 15 days at doses of 0, 50, 100 and 150 mg.L.-1. The variables were evaluated: number of flowers per branch (FLR1-4), number of flowers per plant (FLP1-4),% of fruits retained in phase 3 (FR3),% of fruits retained in phase 5 (FR5), weight of fruits (PF), number of harvested fruits (FC), approximate yield of fruits (RAF), and the real fruit yield (RRF). The design was completely randomized (DCA), in 2x4 factorial arrangement. Defoliation significantly reduced FLP1-4 from 6938 to 3701, while GA3 did not influence that character. Defoliation significantly increased the FR3 retention, but reduced the PF and FC. GA3 significantly influenced FLR1-4, FR3 and PF. In FR5, no statistical difference was recorded for either D or GA3, nor was there significant interaction between the two defoliation and GA3 factors. For FC, RAF and RRF, highly significant differences were found for Defoliation, with superiority of non-defoliated plants but no differences were found for GA3 doses. It is concluded that in F3 the defoliation favored significantly, effect that was diluted in F5, while the application of GA3 negatively influenced this retention. Fruit yield was significantly higher in non-defoliated plants without showing significant difference between GA3 doses.